2016
DOI: 10.1016/j.esxm.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Injection of Hyaluronic Acid in Patients Affected With Peyronie's Disease: Preliminary Results From a Prospective, Multicenter, Pilot Study

Abstract: IntroductionHyaluronic acid has been shown to be efficacious in decreasing scar formation, inflammation, and oxidative stress.AimTo assess the efficacy of intralesional injection of hyaluronic acid in patients affected by Peyronie's disease.MethodsIn this prospective, single-arm, self-controlled, interventional, multicenter pilot study, 65 patients underwent a 10-week cycle of weekly intraplaque injections with hyaluronic acid (0.8% highly purified sodium salt hyaluronic acid 16 mg/2 mL; Sinovial, IBSA, Lodi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 28 publications
4
47
0
1
Order By: Relevance
“…In December 2013 collagenase clostridium histolyticum (CCh/Xiaflex) was approved by the US Food and Drug Administration (FDA) for treatment of Peyronie's disease. Intralesional treatment with HA decreased plaqued size and penile curvature and improved IIEF in a prospective, single arm, self-controlled, interventional, multicentre pilot study on 65 patients (Zucchi et al, 2016). However, this compound has been found to produce the potential occurrence of mild to severe adverse events, including penile ecchymosis, swelling, pain, and corporal rupture (Gelbard et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In December 2013 collagenase clostridium histolyticum (CCh/Xiaflex) was approved by the US Food and Drug Administration (FDA) for treatment of Peyronie's disease. Intralesional treatment with HA decreased plaqued size and penile curvature and improved IIEF in a prospective, single arm, self-controlled, interventional, multicentre pilot study on 65 patients (Zucchi et al, 2016). However, this compound has been found to produce the potential occurrence of mild to severe adverse events, including penile ecchymosis, swelling, pain, and corporal rupture (Gelbard et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These therapeutic options include: oral treatment (potassium para-aminobenzoate, Potaba), vitamin E, colchicine, tamoxifen, carnitine, pentoxifylline, phosphodiesterase type 5 inhibitors); intralesional treatment [steroids, verapamil, collagenase clostridium histolyticum (CCh), interferons]; and topical treatment [extracorporeal shock wave therapy (ESWT), iontophoresis, traction devices and vacuum devices] (Hauck et al, 2006;Safarinejad et al, 2010;Hatzimouratidis et al, 2012;Gelbard et al, 2013;Favilla et al, 2014;Levine et al, 2015;Nehra et al, 2015). Recent prospective, multicenter, pilot study assessing the efficacy of hyaluronic acid (HA) as intralesional treatment for patients with PD showed encouraging preliminary results for improvement of plaque size, penile curvature, and overall sexual satisfaction (Zucchi et al, 2016) and similar results are reported in other study (Gennaro et al, 2015). For this reason, the intralesional therapy with verapamil, for reduced side effects and lower costs, remains the most widely used especially in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to CCH, which main aim is to destroy the plaque, PRP combined with HA is expected to restore normal tissue after digging of small tunnels into TA's fibrotic tissue with a needle (see below). HA alone has been shown to be active on PD in a placebo-controlled study [8]. Preliminary data seems to indicate that a combination of PRP and HA provides better outcomes than HA alone for the treatment of gonarthrosis [19,20] and wound defects [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hyaluronic Acid (HA) (7) and Botulinum toxin [8] have also been proposed with the purpose of counteracting tunica fibrosis, the final issue of the pathological process of PD, before the deposit of calcifications [4]. We hypothesized that regenerative medicine could help stop the process and restore function.…”
Section: Introductionmentioning
confidence: 99%
“…Two retrospective studies and a more recent prospective study have shown a reduction in penile plaque size and curvature, as well as improved penile rigidity. [52][53][54] Botulinum toxin has been shown to reduce fibrosis and scarring. A single study evaluated botulinum toxin A as a treatment for PD and has shown a positive response for safety and improvement in penile curvature, while data from further investigations is pending.…”
Section: Corticosteroidsmentioning
confidence: 99%